Occupational Burnout Symptoms and Its Relationship With Workload and Fear of the SARS-CoV-2 Pandemic Among Hospital Nurses - Marzieh Belji Kangarlou; Farin Fatemi; Fatemeh Paknazar; Alireza Dehdashti; Alireza Dehdashti (Frontiers Media S.A., 2022)
IntroductionThe pandemic has intensified physical and psychological work demands experienced by nurses in a hospital environment. The purpose of this study was to examine personal and work environmental risk factors associated with occupational burnout among hospital nurses.MethodsWe conducted a cross-sectional from April to November 2020. Data from 831 nurses who worked professionally in four educational hospitals were compiled through survey questionnaires to report the prevalence of burnout, occupational and individual factors. Independent t-test and Mann-Whitney test measured the link between the scopes of occupational burnout and risk factors.ResultsAbout half of the participants indicated moderate symptoms of burnout. The fear of the nurses correlated significantly with emotional exhaustion (r = 0.71, p = 0.001), depersonalization (r = 0.67, p = 0.02), and personal accomplishment (r = 0.63, p = 0.05). Mental demand (r = 0.74, p = 0.01) and effort at work (r = 0.68, 0.001) correlated significantly with emotional exhaustion (r = 0.51, p = 0.03).ConclusionThe findings indicated a high prevalence of burnout symptoms, particularly emotional exhaustion, among hospital nursing professionals. Occupational health services should consider burnout as an occupational-related condition and provide interventions to reduce workplace chronic stressors and burnout in hospitals.